SMES Response Strategies and Performance In Covid-19 Pandemics: Implications For Trade And Industry In Computer Village, Lagos, Nigeria - Caroline Aturu-Aghedo; Maurice Aghedo (Eurasian Journal of Management & Social Sciences, 2023)
The global outbreak of COVID-19, commonly referred to as the coronavirus, has profoundly influenced enterprise operations and consumer behaviors. The pandemic’s rapid spread has resulted in immediate socioeconomic repercussions for both industrialized and developing nations. This research explores the impact of the COVID-19 pandemic on enterprise performance within the portable electronic devices sector, focusing on businesses in Computer Village at Ikeja, Lagos. The resource-based theory, behavioral and psychological theory, and strategic adaptation perspective served as the study’s conceptual framework. Descriptive survey research design was used in this study. Data was collected through administering close-ended structured questionnaires. 356 MSMES owners, traders and other stakeholders were drawn through multi-stage sampling technique. Exploratory factor analysis using principal component with varimax rotation, with four factors, which account for 52.438% of total variance and the communalities was used to assess the validity of the scales used for this study. Cronbach’s alpha coefficient reliability of the factors were established: enterprise performance of small businesses (.928), access to innovative assets (.819), entrepreneur’s psychological wellbeing (.781), and available resources (-.253) were established.  Descriptive statistics and regression analysis were used to analyze the data. The findings revealed that enterprise performance is significantly related to access to innovative assets ( = .406, t = 2.229, p = .027; = .605**), psychological wellbeing ( = .223, t = 2.740, p = .027; = .467**), available resources ( = .004, t = 2.740, p = .027; = .172**) and entrepreneurial eco-system ( = -.030, t = 2.740, p = .027; = .112*) during the Covid-19 pandemic.  It is recommended that SME practitioners should consider implementing innovations to enhance their competitiveness, especially innovations with higher novelty that are new to the market, industry, country, and government needs to promote and support research that leads to the creation of new knowledge critical for innovation.